Professors: The Key to Internationalization - Altbach, Philip; Postiglione, Gerard (International Higher Education, 2013)
A key factor in internationalizing any university is the academics who work there. This article notes that analyzes the attitudes of the academic profession and notes that most academics are not very internationally minded. Results from two international studies are used for this analysis.